Green Synthesis of Iron Oxide Nanoparticles (Fe3O4-NPs) using Azadirachta Indica Aqueous Leaf Extract - Izza Taib, Nurul; Abdul Latif, Famiza; Mohamed, Zakiah; Diyana Syazwani Zambri, Nur; ., . (International Journal of Engineering and Technology, 2018)
On treatment of aqueous solutions of ferrous and ferric salts in alkaline medium with Azadirachta indica leaf extract, the rapid formation of stable iron oxide nanoparticles (Fe3O4-NPs) or also known as magnetite nanoparticles is observed to occur. In contrast to previously reported co-precipitation approaches, our synthesis method had utilized a much cheaper and less toxic iron precursor with environmentally benign and non-toxic Azadirachta indica leaf extract was used as a reducing and stabilizing agent. It was found that the presence of various biomolecules such as flavonoids and terpenoids of the aqueous leaf extract plays a major role for the formation of Fe3O4-NPs through infrared spectra analysis. The formation was further confirmed with strong characteristic peak observed at 249 nm for Fe3O4-NPs through UV-Vis spectroscopy. Besides, the shape was mostly spherical and oval. X-Ray Diffraction (XRD) analysis revealed the purity of synthesized Fe3O4-NPs with crystalline cubic structure phase.Â  Transmission Electron Microscopy (TEM) results illustrated that the size and diameter was in the range from 9-14 nm which agrees with calculated Scherrer equation with average diameter of around 11 nm. Vibrating Sample Magnetometer (VSM) analysis indicated that the samples exhibit superparamagnetic with magnetization value was 82 emu/g. Results confirmed this protocol as a simple, rapid, one-step, eco-friendly, non-toxic and hence can be potentially used in various biomedical applications such as magnetic targeting drug delivery system.Â Â